2014
DOI: 10.3389/fnins.2014.00333
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular cues of glucose sensing in the rat olfactory bulb

Abstract: In the brain, glucose homeostasis of extracellular fluid is crucial to the point that systems specifically dedicated to glucose sensing are found in areas involved in energy regulation and feeding behavior. Olfaction is a major sensory modality regulating food consumption. Nutritional status in turn modulates olfactory detection. Recently it has been proposed that some olfactory bulb (OB) neurons respond to glucose similarly to hypothalamic neurons. However, the precise molecular cues governing glucose sensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…) and glucose transporters such as sodium‐glucose transport protein‐1 or insulin sensitive, glucose transporter 4 (Al Koborssy et al . ), of which the latter is known to be regulated by Kv1.3 (Xu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…) and glucose transporters such as sodium‐glucose transport protein‐1 or insulin sensitive, glucose transporter 4 (Al Koborssy et al . ), of which the latter is known to be regulated by Kv1.3 (Xu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…However, behavioral alterations will definitely also be due to changes at more central levels. For instance, the olfactory bulb will be modulated by HFruD since it is extremely sensitive to insulinemia and glycemia 44 45 . The entire OB network and more specifically mitral cells should be modulated 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Postprandially when glucose levels in the blood are high, GLUT4 is expressed on the plasma membrane of dendritic processes. GLUT4 in fasted rats however, is internalized into the cytoplasm (Al Koborssy et al, 2014 ) even though insulin levels in the OB are shown to be 15 fold higher in the fasting state (Fadool et al, 2000 ). Our biochemical data point to a role of Kv1.3 in controlling GLUT4 expression on the membrane but more evidence is needed to prove that this modulation could bypass IR kinase in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In adipocytes, the mechanism of translocation is thought to occur through a PI3K-independent pathway consisting of depolarizing the plasma membrane and increasing the intracellular Ca 2+ concentration (Li et al, 2006 ). The co-localization of GLUT4 and Kv1.3 centrally has not been explored and the mechanism of glucose signaling in the OB has only recently been investigated (Tucker et al, 2013 ; Al Koborssy et al, 2014 ) for such an energy demanding process as odor processing (Carter and Bean, 2009 ; Lecoq et al, 2009 , 2011 ). Kv1.3 currents can be modulated by metabolically active (d-glucose) rather than inactive (l-glucose) glucose in a dose-dependent manner that follows a bell-shaped curve (Tucker et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%